Inhibition of tumor propellant glutathione peroxidase 4 induces ferroptosis in cancer cells and enhances anticancer effect of cisplatin - Zhang, Xuefei; Sui, Shiyao; Wang, Lingling; Li, Haixia; Zhang, Lei; Xu, Shouping; Zheng, Xiulan (Journal of cellular physiology, 2020)
Glutathione peroxidase 4 (GPX4) has been confirmed to inhibit ferroptosis in cancer cells, however, whether GPX4 serves as an oncogene is not clear. In this study, the expression of GPX4 and its influence to survival of patients with cancer were analyzed via public databases. Furthermore, the epigenetic regulation of GPX4 and the relation between GPX4 and chemoresistance of different anticancer drugs was also detected. Most importantly, cytological assays were performed to investigate the function of GPX4 in cancer cells. The results showed that GPX4 was higher expressed in cancer tissues than normal and was negatively associated with prognosis of patients. Furthermore, at upstream of GPX4 there was low DNA methylation sites and enhanced level of H3K4me3 and H3K27ac, indicating that high level of GPX4 in cancer may resulted from epigenetic regulation. Moreover, GPX4 was positively related to chemoresistance of anticancer drugs L‐685458, lapatinib, palbociclib, and topotecan. In addition, GPX4 may potentially be involved in translation of protein, mitochondrial respiratory chain complex I assembly, electron transport oxidative phosphorylation, nonalcoholic fatty liver disease, and metabolic pathways. Finally, we detected that GPX4 inhibited ferroptosis in cancer cells, the inhibition of GPX4 via RSL3 could enhance the anticancer effect of cisplatin in vitro and in vivo. In conclusion, GPX4 acts as an oncogene and inhibits ferroptosis in cancer cells, the anticancer effect of cisplatin can be enhanced by GPX4 inhibition. GPX4 acts as an oncogene and inhibits ferroptosis in cancer cells, the anticancer effect of cisplatin can be enhanced by GPX4 inhibition.